2015
DOI: 10.1080/15384047.2015.1030551
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of pyruvate kinase M2 associates with aggressive clinicopathological features and unfavorable prognosis in oral squamous cell carcinoma

Abstract: Abnormal glucose metabolism mediated by pyruvate kinase M2 (PKM2) fuels cancer overgrowth and propagation. However, its expression and oncogenic roles in in oral squamous cell carcinoma (OSCC) remains incompletely known. Here, we aimed to investigate the expression of PKM2, its prognostic values and oncogenic functions using 7,12-dimethyl-1,2-bezan-tracene (DMBA)-induced hamster buccal pouch SCC model, primary OSCC specimens as well as in vitro cellular assays. We found that in DMBA-induced OSCC model, negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Our results demonstrate that both PKM2 or LDHA are significant prognostic markers in pancreatic cancer and the combination provides improved stratification of outcome. These results are in line with previous publications showing a significant prognostic effect of LDHA or PKM2 in other tumour types, including squamous cell carcinoma, cholangiocarcinoma and gastric cancer [ 43 , 54 , 55 ]. The exact mechanisms associated with the overexpression of PKM2 and LDHA that lead to poor prognosis remain unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Our results demonstrate that both PKM2 or LDHA are significant prognostic markers in pancreatic cancer and the combination provides improved stratification of outcome. These results are in line with previous publications showing a significant prognostic effect of LDHA or PKM2 in other tumour types, including squamous cell carcinoma, cholangiocarcinoma and gastric cancer [ 43 , 54 , 55 ]. The exact mechanisms associated with the overexpression of PKM2 and LDHA that lead to poor prognosis remain unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Pyruvate kinase M2 (PKM2) is a predominant mediator of cancer aerobic glycolysis, and its overexpression has been observed in multiple human cancers including OSCC . As shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…The oncological roles of differentially spliced transcripts of PKM including PKM1 and PKM2, which are mutually exclusive exons 9 and 10 4 , have been previously investigated. It has been reported that overexpression of PKM1/2 isoforms promotes tumorigenesis or induces poor prognoses of patients in multiple cancers 5-17 whereas PKM1 expression in place of PKM2 inhibits tumor cell proliferation 18,19 . Moreover, it has been reported that methylation or deletion of PKM2 promotes tumor progression in liver cancer, breast cancer and medulloblastoma 20-23 .…”
Section: Introductionmentioning
confidence: 99%